SARS‐CoV‐2 and guttate psoriasis: A case report and review of literature. Issue 7 (16th July 2021) - Ali, Elrazi; Mohamed, Abdelaziz; Abuodeh, Joud; Albuni, Mhd Kutaiba; Al‐Mannai, Najlaa; Salameh, Sarah; Petkar, Mahir; Habas, Elmukhtar
Abstract: Guttate psoriasis is a rare dermatological presentation of SARS‐CoV‐2 infection and is seen mainly in patients with an underlying disease psoriasis. Abstract : Guttate psoriasis is a rare dermatological presentation of SARS‐CoV‐2 infection and is seen mainly in patients with an underlying disease psoriasis.